MRI Radiological Predictors of Requiring Microscopic Lumbar Discectomy After Lumbar Disc Herniation. Issue 1 (February 2020) - Varlotta, Christopher G.; Ge, David H.; Stekas, Nicholas; Frangella, Nicholas J.; Manning, Jordan H.; Steinmetz, Leah; Vasquez-Montes, Dennis; Errico, Thomas J.; Bendo, John A.; Kim, Yong H.; Stieber, Jonathan R.; Varlotta, Gerard; et al.
Study Design: Retrospective cohort study. Objective: To investigate radiological differences in lumbar disc herniations (herniated nucleus pulposus [HNP]) between patients receiving microscopic lumbar discectomy (MLD) and nonoperative patients. Methods: Patients with primary treatment for an HNP at a single academic institution between November 2012 to March 2017 were divided into MLD and nonoperative treatment groups. Using magnetic resonance imaging (MRI), axial HNP area; axial canal area; HNP canal compromise; HNP cephalad/caudal migration and HNP MRI signal (black, gray, or mixed) were measured. T test and chi-square analyses compared differences in the groups, binary logistic regression analysis determined odds ratios (ORs), and decision tree analysis compared the cutoff values for risk factors. Results: A total of 285 patients (78 MLD, 207 nonoperative) were included. Risk factors for MLD treatment included larger axial HNP area ( P < .01, OR = 1.01), caudal migration, and migration magnitude ( P < .05, OR = 1.90; P < .01, OR = 1.14), and gray HNP MRI signal ( P < .01, OR = 5.42). Cutoff values for risks included axial HNP area (70.52 mm 2, OR = 2.66, P < .01), HNP canal compromise (20.0%, OR = 3.29, P < .01), and cephalad/caudal migration (6.8 mm, OR = 2.43, P < .01). MLD risk for those with gray HNP MRI signal (67.6% alone) increased when combined with axial HNP area >70.52 mm 2 (75.5%, P = .01) and HNP canal compromise >20.0% (71.1%, P = .05) cutoffs. MLD risk in patients with cephalad/caudal migration >6.8 mm (40.5% alone) increased when combined with axial HNP area and HNP canal compromise (52.4%, 50%; P < .01). Conclusion: Patients who underwent MLD treatment had significantly different axial HNP area, frequency of caudal migration, magnitude of cephalad/caudal migration, and disc herniation MRI signal compared to patients with nonoperative treatment.